2021
DOI: 10.7759/cureus.17823
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Diagnosis of Central Nervous System Tumors: Challenges, Errors, Lessons Learned, and the Surgeon’s Perspective

Abstract: Background: Intraoperative crush smear is an adjuvant in diagnosing central nervous system (CNS) lesions on tissue sent for frozen section. Besides rapid decision-making, it also ensures that minimum injury is caused to the normal brain structures surrounding the intracranial neoplasm. A rapid intraoperative diagnosis helps the surgeon in planning the appropriate surgery.Objective: Our objective is to review all the discordant cases between intraoperative and histopathological diagnosis and also to study the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…Hence a final diagnosis of reactive gliosis was given. Khonglah 18 et al reported same error in their study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Hence a final diagnosis of reactive gliosis was given. Khonglah 18 et al reported same error in their study.…”
Section: Discussionsupporting
confidence: 54%
“…Diagnostic error on cytology was due to sampling from the non-representative area by the surgeon. Khonglah 18 et al also reported case of hemangioblastoma misdiagnosed as low-grade glioma.…”
Section: Discussionmentioning
confidence: 98%